(untitled) (American International Journal of Education and Linguistics Research, 2019)
Distance e-learners are expected to participate in an e-learning environment and interact with the content, colleagues and facilitators through distance education technologies. Learning environment goes a long way to determine student’s academic performance. Hence, this study tends to find out relationship between online interaction and distance e-learners. The purpose of the study was to analyze the correlation that exists between learner-content-interaction (LCI), learner-learner-interaction (LLI) and learner-instructor-interaction (LII) and academic performance of distance e-learners in a Nigerian university. Two research questions were designed to guide the study. A descriptive design of survey type was adopted for the study and a questionnaire was used to collect the quantitative data. The study was conducted in four selected study centres of National Open University of Nigeria (NOUN) and a total of 1,025 participants completed the survey-based questionnaire. The researchers used Spearman’s correlation to determine if correlation exists on each type of interaction. The findings of this study revealed that learner-learner-interaction was the only factor that was significant(r = .066, p-value = .034), with very small weak correlation out of the three types of interactions discussed in this study. Findings also revealed that all the three types of interactions were significant (LCI, r= .121** p=0.009; LII, r=.108*, p=0.018; LLI, r = .105*, p = 0.023) for female distance e-learners but none was significant for male distance e-learners.Based on the findings of the research, recommendations have been made which will assist Nigerian university policy makers and course developers with a view to improving the academic performance of distance e-learners.